INFLIXIMAB-INDUCED LUPUS-LIKE SYNDROME IN A FEMALE PATIENT WITH RHEUMATOID ARTHRITIS (A CASE REPORT): AN ACCIDENT OR REGULARITY? - Yu. V. Muravyev; V. V. Lebedeva; S. Yu. Alamankina (Научно-практическая ревматология, 2017)
The paper describes a case of infliximab-induced lupus-like syndrome in a female patient with rheumatoid arthritis and discusses the possible causes of this pathology.